Postcolonialism and Decoloniality. Resistance and Counter-conducts in the Current Neoliberalism - Luce, Sandro; Marcenò, Serena (Soft Power, 2024)
Post and de-colonial studies define a huge and heterogeneous field of research, crossing several disciplines and territories. Their interdisciplinary interaction produces a fruitful and open space with vague boundaries. Divergent positions, sometimes even contradictory, different ways of being postcolonial prevent us from considering them as a homogeneous entity. However, the heterogeneity of the positions inside and across postcolonial and decolonial studies cannot be separated from a common basis, a core of concepts that move the analysis from the same starting point: the event of colonization.